GASTRONOMIC TOURISM POTENTIAL OF THE SURKHANDARYA REGION (International journal of artificial intelligence, 2026)
This article explores the gastronomic tourism potential of the Surkhandarya region, highlighting the role of unique national dishes in attracting tourists. It analyzes the culinary traditions of the oasis and the possibilities of developing "Surkhoncha" cooking methods as a tourism brand. Finally, the article provides scientific and practical recommendations for creating gastronomic routes in the region.